TINJAUAN KEPUASAN PELANGGAN CAFÉ X DI SURABAYA - Wijaya, Sheline (Universitas Widya Kartika Surabaya, 2024)
Customer satisfaction is a feeling of joy and disappointment that arises after comparing perception with the performance of an expected product. The factor of satisfaction itself is in the quality of the product, the price provided, the service and many more. The existence of customer satisfaction will provide many benefits for the company in question in the form of revenue, word of mouth relationship, and others.This research aims to gain an understanding of customer satisfaction with customers of Surabaya coffee café. This coffee café has quite a lot of customers, but at this time it is difficult to get a loyalty to customers. The number of resource persons used in this study was 10 resource persons using the narrative qualitative data analysis method.The results of this study prove that the customer satisfaction of Café Serlok Kopi Surabaya can be known through the experiences, needs, and expectations they provide. Experience, needs, and expectations are certainly indicators of customer satisfaction that can help customers in providing customer value and can increase their confidence in buying serlok kopi products.